Pseudoaneurysm of Ascending Aorta induced by Brucella Endocarditis In bicuspid Aortic Valve. Issue 6 (20th May 2021) - Liu, Shuo; Ju, Hui; Feng, Yi; Mahmood, Feroze; Dai, Tian; Chen, Yu; Chen, Shenglong; Han, Zengqiang; Fan, Guangpu
Abstract: Brucellosis is endemic in the Mediterranean region, South American countries, and Asia. In China, it is frequently diagnosed in herdsmen who often have contact with livestock. Brucella endocarditis (BE) is a rare complication, but it is the leading reason for mortality. We report a rare case of BE of bicuspid aortic valve with consequent pseudoaneurysm of ascending aorta, which has never been reported before. The major educational value lies in acknowledging a novel presentation of BE which happened in a patient in remission of BE and appreciation of the role of echocardiography in early diagnosis and definitive surgical therapy.